IDENTIFICATION OF HUMAN HAIR USING DIRECT PCR TARGETING THE CYTOCHROME B GENE - Tri Widodo, Wimbuh; Masjkur, Indah Nuraini; Huda, Qurrota A’yunil; Yudianto, Ahmad; Kristianto, Sonny; Putri, Rury Erina (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2024)
Background: Hair is one of the human parts that is easily scattered and easy to obtain for testing. Direct PCR which is PCR without going through the DNA extraction process has been widely used in various fields. The cytochrome b gene is one of the genes located in mitochondrial DNA. The gene is unique in that it has a small variation within one species organism but has a large variation between species. Aims: c. Methods: Hair was heated at 600C for 10 minutes then the sample was used for the PCR template. PCR was performed using the cytochrome b gene. The results: The analysis showed that human hair could still be detected on day 30 using direct PCR using the cytochrome b gene. Conclusions: This result will simplify and save time in analysis in various fields related to hair shafts.